2009
DOI: 10.1002/ddr.20347
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the lipid metabolic pathways for the treatment of malaria

Abstract: The control and eventual eradication of human malaria is considered one of the most important global public health goals of the 21st Century. Malaria, caused by intraerythrocytic protozoan parasites of the genus Plasmodium, is by far the most lethal and among the most prevalent of the infectious diseases. Four species of Plasmodium (P. falciparum, P. malariae, P. ovale, and P. vivax) are known to be infectious to humans, and more recent cases of infection due to P. knowlesi also have been reported. These speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
80
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 83 publications
(106 reference statements)
2
80
0
Order By: Relevance
“…These discoveries reversed the long-held dogma that FAS-II was required for blood stages and, by extension, was an excellent drug target for malaria control due to the absence of FAS-II in the human host (15). Nevertheless, pathways of Plasmodium lipid metabolism remain an attractive target for malaria treatment (16,17). Studies on rodent models of malaria demonstrated that FAS-II was only required for liver-stage development.…”
mentioning
confidence: 98%
“…These discoveries reversed the long-held dogma that FAS-II was required for blood stages and, by extension, was an excellent drug target for malaria control due to the absence of FAS-II in the human host (15). Nevertheless, pathways of Plasmodium lipid metabolism remain an attractive target for malaria treatment (16,17). Studies on rodent models of malaria demonstrated that FAS-II was only required for liver-stage development.…”
mentioning
confidence: 98%
“…The possible emergence of resistance underscores a clear need to find alternative regimens. While several promising agents are in the pipeline, the development of antimalarial drugs that are effective, well tolerated, and safe remains a very challenging task (6,27,77,89). In addition, the new paradigm of antimalarial therapies based on the combination of drugs that have additive or preferably synergistic properties raises the threshold for drug discovery even further.…”
mentioning
confidence: 99%
“…Plasmodium generates PL from polar heads, like choline, ethanolamine or serine (S), which are mainly taken up from the serum (reviewed in Ben Mamoun et al, 2010;Déchamps et al, 2010), whereas phosphatidylinositol (PI) is made by the parasite from inositol that is either taken up from the serum or generated de novo from glucose-6-phosphate via inositol-3-phosphate (reviewed in Ramakrishnan et al, 2013). Phosphatidylethanolamine (PE) is synthesized by the parasite via the phosphorylation of ethanolamine obtained from plasma or through decarboxylation of S (Fig.…”
Section: Membrane Dynamics and Lipid Turnover In Plasmodial Parasitesmentioning
confidence: 99%